2017
DOI: 10.1103/physreve.96.022218
|View full text |Cite
|
Sign up to set email alerts
|

Using missing ordinal patterns to detect nonlinearity in time series data

Abstract: The number of missing ordinal patterns (NMP) is the number of ordinal patterns that do not appear in a series after it has been symbolized using the Bandt and Pompe methodology. In this paper, the NMP is demonstrated as a test for nonlinearity using a surrogate framework in order to see if the NMP for a series is statistically different from the NMP of iterative amplitude adjusted Fourier transform (IAAFT) surrogates. It is found that the NMP works well as a test statistic for nonlinearity, even in the cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 37 publications
3
22
1
Order By: Relevance
“…In contrast, the field of non-linear dynamics has developed measures and models that account for the complexity of the systems and their emerging interactions. [10][11][12][13] These properties are fundamental for the characterization of the thalamo-cortical function and for the emergence of consciousness. 14 A general approach to study time-signals is the characterization of their randomness; for example, by means of the Shannon entropy (SE), 15 which measures the average unpredictability of a signal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the field of non-linear dynamics has developed measures and models that account for the complexity of the systems and their emerging interactions. [10][11][12][13] These properties are fundamental for the characterization of the thalamo-cortical function and for the emergence of consciousness. 14 A general approach to study time-signals is the characterization of their randomness; for example, by means of the Shannon entropy (SE), 15 which measures the average unpredictability of a signal.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to other methods, PeEn is a time-series complexity measure that is simple to implement, is robust to noise and short time-series, and works for arbitrary data sets. 13,16,17,[20][21][22][23][24][25][26] In particular, it has been shown that PeEn applied to EEG signals captures different states associated with the level of consciousness, both during anesthesia [26][27][28][29] and sleep. 30,31 Hence, in order to study the thalamo-cortical function during W and sleep, PeEn is a practical and reliable method, where results can be understood from primary principles, and can be related to the signal characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a higher number of MOPs in the time series under examination compared to IAAFT surrogate data distinguishes deterministic time series from correlated stochastic time series. 41 IAAFT surrogate data are generated such that the surrogate data have the same power spectrum, autocorrelations, and probability distribution with the original time series. As a result, the derived surrogates have the same probability distribution and power spectrum with potential high order correlations being randomized.…”
Section: B Surrogate Datamentioning
confidence: 99%
“…44 To overcome this limitation, Kulp et al used IAAFT surrogate data and the BP MOP paradigm, to detect non-linear determinism in both theoretical and experimental deterministic time series and distinguish them from correlated stochastic time series. 41 There are no studies to date evaluating the ability of the MOP paradigm (as a stand-alone method or in a surrogate data framework) in distinguishing determinism from nonlinear stochastic processes.…”
Section: The Bandt-pompe Symbolization and The Amig O Process For mentioning
confidence: 99%
See 1 more Smart Citation